THE DIFFERENCES OF MUSIC THERAPY AND OXYTOCIN MASSAGE ON POST SECTIO CAESAREAN MOTHERS TO BREASTMILK PRODUCTION IN SALATIGA’S HOSPITAL - Rahma Mafaz Cholishiyyana (Jurnal Komunikasi Kesehatan, 2014)
Background: Exclusive breastfeeding mothers decrease in the post sectioCaesarea. Breastmilk desperately need the prolactin and oxytocin hormone tostimulate expressing milk. Oxytocin massage is the massage on the spine of thescapula costa 5 up to6. Music therapy is a relaxation therapy by listening to theMozart.Purpose: to identify and analyze the different effect of music therapy withoxytocin massage to milk production .Methods: this study used a quasi experiment, post-test with control group design .Place this study in Salatiga’s hospital. The samples were 30 respondents .Instrument research using questionnaires and observation sheets baby weight ,urinate, defecate and long hours of sleep a baby. Analysis of test data using OneWay Anova analysis .Results: the results of this study there is no significant difference between musictherapy and oxytocin massage therapy with resulting P-Value baby’s weight is0.295 ( > 0.05 ), P-Value babyi’s urinate is 0,447 (>0,05), P-Value baby’sdefecation is 0,228 (>0,05), P-Value of baby’s sleep hour is 0,906 (>0,05),